A study of the Application of High Achiever Programs for Gifted Students - Martín-Lobo, Pilar; Pradas Montilla, Silvia; Navarro Asencio, Enrique (Electronic Journal of Research in Educational Psychology, 2019)
Introduction. This research focus on to provide a project for gifted students with enrichment programs that can be performed at the school level. Method. In order to accomplish this, the programs were designed, teachers were trained at six educational centers, 37 gifted students were selected and attention testing was applied (D2); Creating testing (PIC and CREA) and Cognitive Abilities for Solving Interpersonal Problems (Evhocospi) testing were applied before and after performing the Expanded Curriculum, Creative Literature, Scientific World, Creative Mathematics, Art and Culture and Cooperation programs. Results. The results reflect significant improvements in attention, creativity and interpersonal problem resolution in gifted students that participated in the High Achiever Project programs they also reveal new procedures for applying programs for gifted students in the school context Discussion and Conclusion. The intervention program at the expanded curriculum level can be implemented in order to exercise higher intellectual abilities
Estudio de la aplicación de programas de alto rendimiento para alumnos con altas capacidades
Introducción. Esta investigación se enfoca en proporcionar un proyecto para estudiantes dotados con programas de enriquecimiento que se pueden realizar a nivel escolar. Método. Para lograr esto, se diseñaron los programas, se capacitó a los maestros en seis centros educativos, se seleccionaron 37 estudiantes dotados y se aplicaron pruebas de atención (D2); Se aplicaron pruebas de creación (PIC y CREA) y Habilidades cognitivas para resolver problemas interpersonales (Evhocospi) antes y después de la ejecución de los programas Currículo Expandido, Literatura Creativa, Mundo Científico, Matemáticas Creativas, Arte y Cultura y Cooperación. Resultados. Los resultados reflejan mejoras significativas en la atención, la creatividad y la resolución de problemas interpersonales en estudiantes dotados que participaron en los programas del Proyecto High Achiever. También revelan nuevos procedimientos para aplicar programas para estudiantes dotados en el contexto escolar. Discusión y conclusión. El programa de intervención en el nivel de currículo expandido se puede implementar para ejercitar habilidades intelectuales superiors.
Keywords: giftedness; enrichment programs; attention; creativity; interpersonal problems; Emerging; superdotación; programas de enriquecimiento; atención; creatividad; problemas interpersonales; Scopus